Cracks Analysis in the Reinforced Concrete Pipes - Lidia Buda-Ozog; Izabela Skrzypczak; Joanna Kujda (The Baltic Journal of Road and Bridge Engineering, 2017)
In this paper, the analysis of cracking due to tensile stress in a reinforced concrete pipe is presented. The tensile strength of concrete in case of the member of a high relative curvature is significantly different from the strength of uncurved elements. The current state of research indicates that only methods of nonlinear fracture mechanics lead to a satisfactory agreement between the results of calculations and experimental studies, and allow for compiling correctly the influence of basic parameters of stretched concrete and geometrical dimensions on the load capacity of crush pipes made from concrete. Obtaining consistent results of experimental and numerical research is still a very complicated issue. This paper presents the results of the experimental investigation performed on three pipes and the numerical model of the analysed element of the pipes made using the ATENA (Advanced Tool for Engineering Nonlinear Analysis) program. The numerical analyses of cracks were compared with the results of experimental studies.